Development e-worksheet using PjBL on environmental pollution to enhance environmental literacy of tenth grade high school - Wardatul Uyun; S. Suhartini (Research and Development in Education (RaDEn), 2024)
The increasing environmental issues demand environmental literacy among the younger generation. 21st-century learning with PjBL-based worksheet can make the learning process more interactive, contextual, and focused on solving real-world problems. This research aims to:(1) produce an E-worksheet with the PjBL model on environmental pollution that is feasible as a learning model for 10th grade high school; (2) produce an E-worksheet with the PjBL model on environmental pollution that is practically for biological teachers and 10th grade high school; (3) produce an E-worksheet with the PjBL model on environmental pollution that is effective in improving environmental literacy for 10th grade high school. This research uses the R&D mode, specifically the 4D model. The research instruments included interview sheets, practitioner assessment questionnaires, material and media validation sheets, and multiple-choice and descriptive test sheets. Based on the data obtained: (1) The E-worksheet with the PjBL model on the topic of environmental pollution is valid according to material and media experts, scoring in the "very good" category; (2) The E-worksheet is practical based on teacher assessment and student responses with scores included in the “very good” category ; (3) The research results indicate that the N-gain for cognitive domain environmental literacy is (<g> = 0.43) and for the affective domain is (<g> = 0.63), which are categorized as moderate. Based on this, it can be concluded that the Electronic Worksheets (E-worksheet) with the PjBL model is feasible and practical and can enhance the environmental literacy of class X SMA students.